Integrasi media pembelajaran berbasis GeoGebra untuk meningkatkan kemampuan berpikir kritis siswa dalam pembelajaran matematika: Kajian teoritis - Fiqriah, Kamaliatul (Maliki Interdisciplinary Journal, 2026)
Critical thinking in mathematics is a fundamental skill that students must develop to meet the demands of the 21st century. Nevertheless, international assessments such as PISA and TIMSS reveal that Indonesian students’ performance in mathematics remains below expectations. An effective approach to address this issue is the integration of technology-based innovative learning tools, particularly the GeoGebra software, into mathematics instruction. This paper seeks to provide a theoretical review of how GeoGebra can be utilized as a learning medium to enhance students’ critical thinking abilities in mathematics. The study employs a literature review method with a descriptive-analytical framework. Findings indicate that GeoGebra offers dynamic visualizations of abstract mathematical concepts, fosters independent exploration, and creates cognitive conditions that stimulate critical thinking. Its application in teaching geometry, algebra, and calculus has been shown to significantly improve students’ active participation and mathematical reasoning. The study recommends strengthening teachers’ competencies in using GeoGebra and developing GeoGebra-based instructional materials aligned with the current curriculum.